2007
DOI: 10.1093/carcin/bgm130
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid and its synthetic derivative CADPE suppress tumor angiogenesis by blocking STAT3-mediated VEGF expression in human renal carcinoma cells

Abstract: Tumor angiogenesis is required for tumor development and is stimulated by angiogenic inducers like VEGF (vascular endothelial growth factor). Our previous study demonstrated that STAT3 (signal transducer and activator of transcription 3) up-regulates HIF-1alpha (hypoxia inducible factor-1alpha) protein stability and enhances HIF-1-mediated VEGF expression in hypoxic solid tumor cells, thus suggesting that the inhibition of STAT3 signaling may have clinical applications. In this study, we examined in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 32 publications
4
100
1
Order By: Relevance
“…S6), Moreover, in the CADPE-treated groups, CADPE had little effect on body weight at the concentrations tested at 3 months (Fig. 4F), which is consistent with a previous report, (24) suggesting little toxicity of CADPE at the tested concentration.…”
Section: Cadpe Inhibits Rankl-induced Actin-ring Formation In Osteoclsupporting
confidence: 91%
See 2 more Smart Citations
“…S6), Moreover, in the CADPE-treated groups, CADPE had little effect on body weight at the concentrations tested at 3 months (Fig. 4F), which is consistent with a previous report, (24) suggesting little toxicity of CADPE at the tested concentration.…”
Section: Cadpe Inhibits Rankl-induced Actin-ring Formation In Osteoclsupporting
confidence: 91%
“…(39) CADPE has been demonstrated to be effective in inducing tumor cell senescence and suppression of tumor growth, invasion, and angiogenesis. (23,24) However, its inhibitory effect on osteoclastogenesis and the molecular mechanism(s) are unknown. In this report, we demonstrated that CADPE Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the critical roles of STAT3 signaling in the angiogenic and neoplastic process (20,21), we screened a number of natural compounds and found that nitidine chloride exerted its antiangiogenic and antitumor property through the suppression of STAT3 pathway. We provide evidence that nitidine chloride dose dependently suppresses the activation of STAT3, its DNA-binding activity, and its transcriptional activity in both human endothelial cells and gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the anticarcinogenic effects of propolis encouraged efforts to identify, isolate and synthesize constituents of propolis and to study their effects and mechanisms of action, including artepillin C 11 , caffeic acid 12 , caffeic acid phenethyl ester 13 , and in the present study, we used an in vivo model to evaluate the effect of intragastric administration of green propolis (in the form of WSDP) on angiogenesis in BBN-induced rat bladder cancer.…”
Section: Introductionmentioning
confidence: 99%